Climate versus trade? Reconciling international subsidy rules with industrial decarbonisation - David Kleimann (Bruegel, 2023)
The vast environmental subsidies that may be required for the transition to net-zero greenhouse gas emissions are starting to generate international trade and political frictions between the world's largest economies. This puts (supra-)national industrial decarbonisation efforts on a collision course with international subsidies rules and national countervailing duty (ie anti-foreign subsidy) laws and regulations. International cooperation will be essential to defuse such tensions before they escalate and impede effective climate policy rollouts, and before they lead to economic countermeasures that create new barriers to trade in environmental goods. This requires agreement on permissible environmental subsidy practices that minimise distortions. Meanwhile, it will be crucial to provide financial transfers to assist poorer economies with industrial decarbonisation at the same time as those poorer economies are suffering from the cross-border negative economic impacts of otherwise net-global-welfare enhancing environmental subsidies paid out by wealthy countries. Various forums can host the technical and political negotiations necessary to set the parameters of net global-welfare enhancing subsidies. These include the G7, the G20, the Organisation for Economic Co-operation and Development, the World Trade Organisation's Trade and Environment Committee and WTO Trade and Environmental Sustainability Structured Discussions, and the Coalition of Trade Ministers on Climate.
Keywords: 330